2017
DOI: 10.15252/embj.201696048
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipid metabolic flow controls phosphoinositide turnover at the trans ‐Golgi network

Abstract: Abstract:Sphingolipids are membrane lipids, which are globally required for eukaryotic life.Sphingolipid composition varies among endomembranes with pre-and post-Golgi compartments being poor and rich in sphingolipids, respectively. Thanks to this different sphingolipid content, pre-and post-Golgi membranes serve different cellular functions.Nevertheless, how subcellular sphingolipid levels are maintained in spite of trafficking and metabolic fluxes is only partially understood. Here we describe a homeostatic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 76 publications
(135 reference statements)
4
65
0
Order By: Relevance
“…Based on rates of label incorporation into 17 carbon-sphingolipid metabolites during a 120 min precursor pulse, we identified discrete phases of synthesis of sphingolipid metabolites that correspond to the enzymatic activities for CerS, DeS, HexCer, and SM synthesis in MCF-7 breast cancer cells. These kinetic results also agree with what is currently known about the subcellular localization of de novo synthesis of sphingolipids [36,[38][39][40]. Notably, all results were acquired from a single-step approach utilizing a 17 carbon-sphingoid label that demonstrates very similar biochemical properties to the endogenous substrates; as such, all obtained metabolic rates are comparable to those of natural sphingolipids.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on rates of label incorporation into 17 carbon-sphingolipid metabolites during a 120 min precursor pulse, we identified discrete phases of synthesis of sphingolipid metabolites that correspond to the enzymatic activities for CerS, DeS, HexCer, and SM synthesis in MCF-7 breast cancer cells. These kinetic results also agree with what is currently known about the subcellular localization of de novo synthesis of sphingolipids [36,[38][39][40]. Notably, all results were acquired from a single-step approach utilizing a 17 carbon-sphingoid label that demonstrates very similar biochemical properties to the endogenous substrates; as such, all obtained metabolic rates are comparable to those of natural sphingolipids.…”
Section: Discussionsupporting
confidence: 86%
“…Our data demonstrate that generation of d17SM and d17HexCer occur at relatively the same rate and with similar initial incorporation of our label (Fig 6). Thus, utilizing it has been reported that BFA treatment enhanced incorporation of short chain ceramides into short chain SM while the conversion into short chain HexCer was unchanged [39,49]. In our study, BFA decreased the time the d17Cer took to reach SMS enzymes from 35 min to 5 min suggesting that 30 min is approximately the time necessary for Cer to reach SMS in the Golgi from the ER (Fig 6E).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…3). D'Angelo et al recently showed that the sustained sphingolipid inflow into the trans-Golgi regions reduces the level of PtdIns(4)P at the trans-Golgi regions, which causes the down-regulation of Golgi-targeting of CERT and consequently represses SM biosynthesis [64]. The reduction in PtdIns(4)P level is dependent on SMS, PKD, OSBP and SAC1 [64].…”
Section: Various Factors Involved In the Regulation Of Certmentioning
confidence: 99%
“…D'Angelo et al recently showed that the sustained sphingolipid inflow into the trans-Golgi regions reduces the level of PtdIns(4)P at the trans-Golgi regions, which causes the down-regulation of Golgi-targeting of CERT and consequently represses SM biosynthesis [64]. The reduction in PtdIns(4)P level is dependent on SMS, PKD, OSBP and SAC1 [64]. When a water-miscible short-chain ceramide was exogenously added to cultured cells, it was converted to short-chain SM in the Golgi complex by SMS with an equimolar generation of DAG in a CERT-independent manner.…”
Section: Various Factors Involved In the Regulation Of Certmentioning
confidence: 99%